ANALISIS RELIGIUSITAS, PEMAHAMAN PRODUK DAN SISTIM PEMBIAYAAN SYARIAH DENGAN SIKAP PENGUSAHA - R. Ery Wibowo Agung Santosa (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2015)
Along with the movement launched by the government of Islamic economics in 2013 it shows that Islamic economic sector shows an important role in sustaining economic growth. Islamic banks isone of the pillars of the economy which is expected to drive economic growth through strengthening capital. It is important for entrepreneurs to understand the products and financing mechanisms syariah. The syaria bank is expected can establish a joint venture partner with a productive entrepreneur. The main purpose of research iniadalah analyze the effect of understanding of the product and the financing system for the results in the Islamic bank with the attitude of entrepreneur towards financing inIslamic banks through relegiusitas as pemoderating. It is hoped this can spur the growth of Islamic finance which have a direct impact on national economic growth. The population is Muslim businessman in Semarang. The data samples are taken using the method of questionnaire survey (self-report) and then analyzed using multiple regression to test the hypothesis of the absolute value of the difference Frucot andShearon. Outcomes of this study are expected to add to the enrichment of teaching materials for academics, increase the repertoire of research on Shariah-based banking system, contribute ideas and research resultsto the managers of Islamic banking, contribute ideas and empirical evidence to researchers about the continued operation of Islamic banks Keywords : Relegiusitas, attitude,understanding